PELAKSANAAN PERJANJIAN ANTARA PT.TELKOM DENGAN PELANGGAN INDIHOME DALAM PEMBERIAN JASA LAYANAN INTENET DI PEKANBARU - Arrahman Arsista; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
IndiHome is one of the service products of PT. Telekomunikasi Indonesia in the form of communication and data service packages such as landlines (voice), internet (internet on Fiber or High Speed Internet), and interactive television services (USee TV Cable, IP TV). people who start subscribing, the more problems that arise. Installation of the IndiHome tool which has to wait a long time and the imposition of erratic rates that sometimes burdens customers as well as the handling of protracted customer complaints. In fact, customers still do not want to continue payments because they already feel disadvantaged, and customers are required to return the modem that has been lent by PT Telkom.The research carried out is sociological legal research, namely research that starts on the process of revealing the truth based on the use of basic concepts known in sociology as science, and is taken from secondary data by processing data from primary legal materials, secondary legal materials, and materials. tertiary law. Research location in Pekanbaru Riau. The approach used is a juridical-sociological approach, which is research conducted on real conditions in the environment of Pekanbaru City, especially in Sail District.The results of this study regarding the implementation of the agreement between PT.Telkom and IndiHome customers in providing Internet services in Pekanbaru have not been fully implemented properly, the customer's lack of knowledge of the Agreement which causes the Default. The effort made by PT. Telkom is waiting for the good faith of the customer in returning the equipment (ONT / Modem / STB) that was installed at the customer's house is OWNED by TELKOM which was lent while being a TELKOM customer. Modems that are not used due to migration to fiber are pulled back.Keywords : subscription agreement, customer